Development of CdCl2 Activation to Minimize Zn Loss from Sputtered Cd1-xZnxTe Thin Films for Use in Tandem Solar Cells. (12th July 2018) - Alfadhili, Fadhil K.; Liyanage, Geethika K.; Phillips, Adam B.; Heben, Michael J.
ABSTRACT: Increasing the band gap of cadmium telluride (CdTe) from 1.48 eV to > 2 eV can be achieved by alloying CdTe with ZnTe. Like CdTe, the alloyed films are expected to allow for low cost production, suggesting that Cd1-x Znx Te could be an ideal top cell for mass produced tandem devices. However, the CdCl2 activation of the alloyed films results in a significant loss of Zn, thereby reducing the bandgap. In this study, we demonstrate a novel CdCl2 activation method that does not result in significant Zn loss. By performing the activation step in a closed, inert environment we are able to avoid oxidation of the Zn in the Cd1-x Znx Te film; furthermore, by including sacrificial Zn in the container, an overpressure of ZnCl2 forms limiting the amount of ZnCl2 formed in the film. Both x-ray diffraction, optical measurements, and Auger spectroscopy show that the CdCl2 treatment with no flowing gas minimizes the loss of Zn from the CZT alloy.